Gestión administrativa financiera y su efecto en la rentabilidad de importadora Imporbrands s.a. del Cantón Quevedo, Periodo 2013-2014. Sistema de gestión. - Alcívar Saltos, Maritza Elizabeth (2016)
Financial administration management is an element of the general administration that is very important for the operation of any business. Therefore, it becomes a tool in the development of planning, management, control, direction and financial activities done by the administrators. To fulfil the issues raised in this research, and to respond to the problems found and the objectives stated, it is important to establish the theoretical foundation covering the theoretical, conceptual and legal groundwork that provides the scientific support. Several techniques were utilized to obtain the needed information including: i) surveys answered by customers of the company IMPORBRANDS S.A., in order to know the internal administrative system, ii) interviews apply to the directors of the company, iii) focus groups developed for the construction of the SWOT matrix to obtain information to comply with the hypothesis. And, consequently to allow the projected recommendations of this investigation to mitigate the problems founds in the company. According to the results, it was determined that the majority of clients are satisfied with the services and quality of the products received. However, clients consider prices are in the category of medium-high in relation to the market of automotive brakes of Quevedo. Clients also point out that the company needs to have a yard for repairs and maintenance. It was also determined that though the company guarantees the quality of its products and services, it does not have a suitable organizational structure or employee manual so that employees are guided by the requirements of the manager. The above generates discomfort in employees having to improvise tasks. It also stands out the need to expand the workspace and implement strategies to improve operations. In the positive side, employees leave evidence that the equipment is high-tech and they have an efficient software for administration and finances. The company does not have an employee manual handbook. However, by common sense, it is considered that the vertical management structure allows the manager to decide what best suits the performance of the workers. It is noticeable the permanent training to the human talent as well as the employees benefits by law though with small delays in the payment of salaries and incentives. The data reviewed in the system and the company’s financial documentation shows a weak monetary situation but it has a large amount of inventory. This inventory rotates slowly with the risk of not meeting with the company’s obligations. It also does not have strategies to provide credit nor to collect debts. Applying the financial administrative process, it is proposed to implement a management system that offers, the company’s directors and others involved, a road to become more efficient and meet the social purpose of the design of the company. Design that is based on the theoretical foundation, providing quality experiences in the business of automotive brakes, through practices that are vital to achieve the desired objectives.